TAFSIR FORCE MAJEURE TERHADAP PERISTIWA COVID-19 SEBAGAI DASAR PEMBATALAN KONTRAK BISNIS - Firmansyah, Muhammad Agam; Wahyoeono, Dipo (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
The aim of this research is to identify the corona virus as an abnormal public failure on the basis of a contractual force majeure. the author in this case uses or chooses a type of normative research based on the results obtained indirectly. The author in terms of compiling journals also uses the concept method approach. Through analysis of qualitative descriptive data and literature search, legal material collection techniques were obtained. Products obtained from research exposing, pandemic Non-natural national disaster corona virus is used as the basis for a force majeure that results in or is used as a reason for canceling an agreement. However, the corona virus pandemic can be used as a direct basis for the inability of one of the parties to fulfill obligations provided that it must prove that the inability is directly caused by the influence of the corona virus. Therefore, the corona virus pandemic can be remembered for the terms of understanding relative force majeure